Effective change management and engagement strategies for Nottingham Forest to make it a successful Multi-Channel retailer - Dube, Nipun (2008)
As football fans and also business students with particular interest in retail strategy, the opportunity to work with Nottingham Forest in that capacity was appropriate. Nottingham Forest Football Club is concerned with the level of sales and revenue it makes from merchandise sales, across all retail channels. In tackling this issue, it was important to understand the shift in football from being just about entertainment but more about a business which not only pays for itself but also makes profit. Key to this shift is the knowledge that although football's (and sports in general) offering is intangible (i.e. it provides entertainment and a sense of belonging and attachment); it is this very intangibility that provides the basis for tangible cues. Tangible cues are physical signs and signals use to represent or direct to a non tangible service. The success of these tangible cues is dependent on the value attached to the club by the fans; that is, the loyalty of the fans to the brand. It was also pertinent to note that in retailing, it is important to incorporate the various channels available. Most effective retail organizations have incorporated successful multi-channel retailing. These channels include the retail store, the online store, catalogues and telephone. If any of the channels is viewed uncharitably by customers (in this case the fans), it could and does affect the rest of the channels. Channel conflict is not tolerable in present day retail strategy. The report also focuses on the change management issues and the engagement strategy that can be very effectively and efficiently utilized by the clubs. The key is to understand the drivers for change, identify the change champions and the level of engagement of its employees and also, the communication happening from the top management to the employees.